PARADOKS PURBAYA EFFECT: FENOMENA BOTTLENECK PEMBIAYAAN SEKTOR UMKM DI TENGAH LIKUIDITAS JUMBO DAN PERSPEKTIF EKONOMI ISLAM - Setyadi, Wendi Hadi; Irham Asfy Putra; Dwi Surya Atmaja; Luqman Luqman (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The liquidity injection policy utilizing the Accumulated Budget Surplus (SAL) of IDR 200 trillion aims to create the "Purbaya Effect" to lower the Cost of Funds and stimulate the real sector. However, this research uncovers a policy transmission paradox. This study aims to analyze the bottleneck phenomenon in capital flows to the MSME sector and evaluate its compatibility with Sharia distribution principles. Employing a descriptive-qualitative method with secondary data from January to December 2025, this study reveals significant anomalies. Although the Cost of Funds successfully declined, data shows a sharp disparity: corporate credit grew rapidly, while MSME credit experienced a contraction, plummeting from 4.1% growth (January 2025) to -0.9% (December 2025). These findings indicate that the bottleneck resulted from banking risk aversion and the MSMEs' lack of capacity to absorb this liquidity abundance. From an Islamic economic perspective, this condition points to the practice of "Institutional Ikniz" (hoarding), which violates distributive justice. This study recommends a paradigm shift from mere liquidity injection toward ecosystem strengthening through massive capacity building to mitigate market failure risks.